Knowledge and Behavior of Saudi College Athletes toward Energy and Sports Drinks with an Emphasis on Microbial Quality and Safety - Sulaiman Omar Aljaloud (MDPI AG, 2018)
The aim of this study was to assess the knowledge and behavior of university athletes in Saudi Arabia regarding energy drinks (EDs) and sports drinks (SDs). In addition, the microbiological quality of available local drinks was also assessed. The presence of total bacterial coliform count, Escherichia coli, Salmonella, and Staphylococcus aureus on these drinks was also determined. Of the 120 university athletes surveyed, 69 were currently using SDs, and 51 were using EDs. The study consisted of a 10-question survey assessing the athletes’ sociodemographic characteristics, personal habits, and SD- and ED-related knowledge and habits. With regard to the question about the primary reason for using EDs, n = 26 respondents (50.98%) reported that providing energy (speed, strength, and power) was the main reason for consuming these beverages. Conversely, n = 25 respondents (36.23%) believed that recovery from injury or illnesses was the main reason for the consumption of SDs. A majority of university athletes (n = 43, 62.32%) who used SDs believed that SDs were safe to use, while n = 22 respondents (43.14%) were unaware of any adverse health effects associated with the consumption of EDs. Of the total of 26 SDs and EDs tested, microbial contamination was present in only two products. Microbial levels and the total bacterial count for most of the samples were very low (<1 log CFU/mL). However, some drinks had a slightly higher microbial level, which could be harmful or cause spoilage with improper storage. Thus, our findings suggest that improvements in microbial quality are needed for these beverages.